Implementation of the Outcome-Based Education Curriculum in the Development of Islamic Character of Students in the Islamic Primary Teacher Education Program - Nuryanto, Nuryanto; Priyantoro, Dian Eka; Arifin, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to describe the implementation of the Outcome-Based Education Curriculum (OBE) in the development of the Islamic character of students of the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI) at UIN Jurai Siwo Lampung. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews with PGMI study program leaders and lecturers, observation of the learning process, and analysis of curriculum documents, which included Graduate Learning Outcomes (CPL), Semester Learning Plans (RPS), and assessment instruments. Data analysis was carried out thematically with data reduction techniques, data presentation, and a conclusion drawn, and validated through triangulation of sources and techniques. The study reveals that the OBE curriculum in the PGMI program has successfully integrated Islamic character values, faith (tawḥīd), morality (akhlāq), and social responsibility into graduate learning outcomes and active learning strategies. However, implementation remains suboptimal due to uneven faculty understanding of the OBE paradigm and a lack of standardized instruments for measuring affective and spiritual growth. This research concludes that while OBE effectively fosters 21st-century skills aligned with Islamic values, its success in character building fundamentally requires systematic enhancement of lecturer capacity and the development of structured, contextual assessment tools.